Aerial e-mobility perspective: Anticipated designs and operational capabilities of eVTOL urban air mobility (UAM) aircraft - Marzouk, Osama A. (Edelweiss Applied Science and Technology, 2025)
We collected data about 13 urban air mobility (UAM) electric vertical take-off and landing (eVTOL) aircraft from 12 UAM companies in the world. While none of these models has yet reached a large-scale commercial operation (particularly as air taxis), some of them progressed well in the certification process and may have their UAM models widely operated within a few years. This article focuses on the variability in the configurations of these UAM eVTOL aircraft for aerial e-mobility; such as single-fixed-wing, tandem-tilt-wing, canard wing, fixed-rotor fixed-wing, full tilt-rotor, partial tilt-rotor, V-shaped tail, tailless, twin tail, conventional tail assembly, distributed propulsion, multicopter, rear forward thrust propeller, ducted fans, and a hybrid airplane-helicopter design. The 13 UAM eVTOL aircraft covered here are: (1) EH216-S (by EHang), (2) VoloCity (by Volocopter), (3) Lilium Jet (by Lilium), (4) VoloRegion (by Volocopter), (5) CityAirbus NextGen (by Airbus), (6) Passenger Air Vehicle - PAV (by Boeing), (7) S-A2 (by Hyundai), (8) Joby (by Joby Aviation), (9) VX4 (by Vertical Aerospace Group), (10) Midnight (by Archer Aviation), (11) Eve (by Eve Air Mobility), (12) Jaunt (by Jaunt Air Mobility), and (13) Generation 6 (by Wisk Aero). Out of these 13 UAM eVTOL aircraft models for aerial e-mobility and/or air taxis, we found that 11 models utilize a wing configuration, while only two use a wingless multirotor concept (as in hobbyist drones). A fixed-wing design is associated with a faster travel speed, at the expense of added restrictions on maneuvering and low-speed travel (or hovering). Six models are intended to have an onboard human pilot, while the remaining seven models are designed to be pilotless. One model demonstrated the ability to use hydrogen as a clean source of energy through a fuel cell system.